Zakat Based Sociopreneurship: Eradicating the Poverty of the Rural Poor through the National Amil Zakat Agency of Gresik Regency - Mugiyati, Mugiyati; Mutitul Choiroh, Ifa (Management of Zakat and Waqf Journal (MAZAWA), 2024)
this research aims to develop sociopreneurship-based zakat funds in rural poor communities through mentoring to achieve welfare. So far, many allocations of zakat funds have not developed and have no change for the poor. The research method used is qualitative with the Asset Basic Community Development (ABCD) approach. The mentoring method is carried out with a transformative and participatory approach. The mentoring team is only a facilitator to accelerate the community towards a more prosperous economic condition. The results found that the practice of zakat-based sociopreneurship was implemented with two schemes, namely: First, microfinance programme in the form of providing business capital for mustahik micro business actors. Second, business facilities assistance programme in the form of production facilities such as machinery or livestock needed by mustahik. Assistance in building the sustainability of the sociopreneurship programme is carried out through five steps: (1). Focus group discussion (FGD), (2) Stakeholder involvement (3). Training. (4). Measurement of the effectiveness of sociopreneurship.